2008
DOI: 10.1007/s00221-008-1681-5
|View full text |Cite
|
Sign up to set email alerts
|

The serial reaction time task revisited: a study on motor sequence learning with an arm-reaching task

Abstract: With a series of novel arm-reaching tasks, we have shown that visuomotor sequence learning encompasses the acquisition of the order of sequence elements, and the ability to combine them in a single, skilled behavior. The first component, which is mostly declarative, is reflected by changes in movement onset time (OT); the second, which occurs without subject’s awareness, is measured by changes in kinematic variables, including movement time (MT). Key-press-based serial reaction time tasks (SRTT) have been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 22 publications
(60 reference statements)
5
95
2
1
Order By: Relevance
“…Thus, we think that the reduction in the total process time to final motor response may be attributed to the rapid onsets of muscle activation and movement initiation as motor sequential learning progressed. Our findings, showing a decline in total processing times, were in line with previous learning experiments with the SRT task, which exhibit a gradual reduction of the reaction time 5,11,12,15,16) . It has previously been established that motor sequential learning is accomplished by acquisition of explicit and implicit knowledge in multiple brain areas, including the cortical and subcortical structures 2,[17][18][19] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, we think that the reduction in the total process time to final motor response may be attributed to the rapid onsets of muscle activation and movement initiation as motor sequential learning progressed. Our findings, showing a decline in total processing times, were in line with previous learning experiments with the SRT task, which exhibit a gradual reduction of the reaction time 5,11,12,15,16) . It has previously been established that motor sequential learning is accomplished by acquisition of explicit and implicit knowledge in multiple brain areas, including the cortical and subcortical structures 2,[17][18][19] .…”
Section: Discussionsupporting
confidence: 92%
“…In a tanscranial magnetic stimulation (TMS) experiment by Krutky and Perreault 17) , changes in TMS-evoked muscle activity and joint movement were taken as evidence of short-term corticomotor plasticity after repetitive practice of a simple movement by the upper limb. Apart from providing evidence of neural processing, several prior studies have reported that movement onset time was reduced by motor sequential learning or physical exercise 7,11,[23][24] . Thus, we speculate that earlier onset of EMG activity and actual movement could result in reduction of the total processing time through efficient neural and neuromuscular processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, sequential motor tasks include two components: the acquisition of the order of the elements in the sequence, and the ability to perform fast and accurately each element of the sequence. Three experimental paradigms have been proposed to investigate sequential learning: 1) the serial reaction time task (SRTT), in which the acquisition of the sequence order is inferred from a reduction in response time (Goedert and Willingham 2002), 2) the measurement of improvement in speed and accuracy (as in our motor task) of a previously learned sequence; this task emphasizes acquisition of the sequence elements rather than acquisition of sequence order (Walker et al 2003(Walker et al 2002; 3) the explicit learning of motor sequence, in which the two components of sequence learning can be quantified separately Moisello et al 2009). …”
Section: Sequential Order Learning Versus Improvement Of the Sequencementioning
confidence: 99%
“…First, in previous studies, chunk or statistical learning was measured by response time. We examined two phases of response time: reaction time (RT), which reflects mental processing (Sternberg, 1969), and movement time (MT), which characterizes the movement itself (Moisello et al, 2009). It is essential to understand whether chunk or statistical learning found in previous studies was attributed to RT and/or MT patterns.…”
Section: Introductionmentioning
confidence: 99%